Excision repair of ultraviolet-irradiated deoxyribonucleic acid in plasmolyzed cells of Escherichia coli. - Seeberg, E (1976)
A system of cells made permeable by treatment with high concentrations of surcrose (plasmolysis) has been exploited to study the excision repair of ultraviolet-irradiated deoxyribonucleic acid in Escherichia coli. It is demonstrated that adenosine 5'-triphosphate is required for incision breaks to be made in the bacterial chromosome as well as in covalently closed bacteriophage lambda deoxyribonucleic acid. After plasmolysis, uvrC mutant strains appear as defective in the incision step as the uvrA-mutated strains. This is in contrast to the situation in intact cells where uvrC mutants accumulate single-strand breaks during postirradiation incubation. These observations have led to the proposal of a model for excision repair, in which the ultraviolet-specific endonuclease, coded for by the uvrA and uvrB genes, exists in a complex with the uvrC gene product. The complex is responsible for the incision and possibly also the excision steps of repair. The dark-repair inhibitors acriflavine and caffeine are both shown to interfere with the action of the adenosine 5'-triphosphate-dependent enzyme.